Case Report: Prenatal diagnosis of 10 fetuses with 15q11-q13 duplication and pregnancy outcome in a cohort of Chinese women - Wu, Ke; Li, Xiao; Zhou, Hongmei; Cong, Yan (Frontiers in Neuroscience, 2025)
The chromosome 15q11-q13 duplication (dup15q) is defined as the presence of three or more copies of 15q11.2-q13.1. The features of the chromosome 15q11-q13 duplication syndrome include developmental delay, intellectual disability, hypotonia, facial anomalies, autism spectrum disorder, seizures, and behavioral problems. To date, more than 120 cases of 15q11-q13 duplication have been reported, but studies on clinical information about prenatal diagnosis of 15q11-q13 duplication and attitudes toward fetuses with 15q11-q13 duplication are extremely limited. Herein, we first report a retrospective Chinese cohort with prenatal diagnosis of 15q11-q13 duplication involving ten phenotypically normal pregnant women. In this Chinese cohort, most of fetuses (90%) with 15q11-q13 duplications did not have ultrasound abnormalities. Although the penetrance of 15q11-q13 duplication appeared to be incomplete, 60% of families opted to terminate the pregnancy due to concerns about potential risks. Not all 15q11-q13 duplications were attributed to the parental inheritance, 15q11-q13 duplications could also be caused by parental genomic structure variation. We hope that this study provides new and useful insights into the prenatal diagnosis of 15q11-q13 duplication, thereby informing genetic counseling and decision-making regarding pregnancy outcomes.